Hubungan Kematangan Emosional dengan Forgiveness pada Mahasiswa Psikologi UNP - Deby Amanda Puri; Asri Rima Oktavia; Nuzul Khaira; Kania Jeanrita; Rida Yanna Primanita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to explore the relationship between emotional maturity and forgiveness in Psychology students of Padang State University. This study applies a quantitative approach with a correlational design involving 100 students as respondents selected using incidental sampling techniques. The results of data analysis show a significance value of 0.000 (p <0.05) strengthening that the relationship between emotional maturity and forgiveness is statistically significant. This finding reveals that the higher the level of emotional maturity of students, the better their ability in forgiveness.